2020
DOI: 10.1039/c9cp06798a
|View full text |Cite
|
Sign up to set email alerts
|

Glucose in dry and moist ionic liquid: vibrational circular dichroism, IR, and possible mechanisms

Abstract: The molecular level specification of glucose monomers in ionic liquids and their mixtures with water helps understanding cellulose processing in these liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 69 publications
2
24
1
Order By: Relevance
“…In order to dissolve cellulose, a solvent needs to break up the hydrogen bond network between the polymer strands [25] and replace it by hydrogen bonds to the solvent [8]. Most of the ILs proposed as cellulose solvents are based on imidazolium cations [10,[25][26][27][28], which is not surprising, as it has been known for long that many imidazolium-based ILs form very strong hydrogen bonds [29][30][31][32][33][34][35][36]. Some of these imidazolium-based ILs are able to dissolve more than 20 wt.-% of cellulose if the anions are strong hydrogen bond acceptors [3,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…In order to dissolve cellulose, a solvent needs to break up the hydrogen bond network between the polymer strands [25] and replace it by hydrogen bonds to the solvent [8]. Most of the ILs proposed as cellulose solvents are based on imidazolium cations [10,[25][26][27][28], which is not surprising, as it has been known for long that many imidazolium-based ILs form very strong hydrogen bonds [29][30][31][32][33][34][35][36]. Some of these imidazolium-based ILs are able to dissolve more than 20 wt.-% of cellulose if the anions are strong hydrogen bond acceptors [3,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Nolan and co‐workers reported that the NHC–metal complexes from imidazolium salts and metal ions can form through an analogous path, in which the preparation or even the in situ generation of an NHC is unnecessary, allowing very simple synthetic routes to these practically highly important compounds . Regarding the carbene‐like reactions of imidazolium acetate ionic liquids with glucose, we found indications that the concerted mechanism should be prevalent, as the aggregates that are required for the associative mechanism spontaneously occurred in ab initio molecular dynamics simulations, whereas the barriers of this mechanism were somewhat lower than that of the reaction through carbene intermediates . However, we found that in such an ionic liquid environment, and with the acetate anion as base the difference between these two mechanisms in barriers is lower, which implies that there might be experimental setups, in which the dissociative mechanism is more facile.…”
Section: Introductionmentioning
confidence: 73%
“…The positive charge on the azolium cations is delocalized over the whole ring, whereas on the ammonium cation it is highly localized on the N−H unit. Therefore, although azolium cations have also been shown to be hydrogen‐bond donors, ammonium cations offer an even stronger donor site. These differences are clearly observable in the electrostatic potential maps of the azolium and ammonium ions, as well as the charges of the hydrogen bond donor sites (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this approach, the electron density is stored at each time step so that finite differences with respect to the time propagation can be applied afterwards 169 . They applied their method to the IR and VCD spectra of (R)‐2‐butanol solution in carbon disulfide 130,169 and glucose in an ionic liquid 170 …”
Section: Types Of Spectroscopymentioning
confidence: 99%